Motor Preparation for Action Inhibition: A Review of Single Pulse TMS Studies Using the Go/NoGo Paradigm - Ficarella, Stefania C.; Battelli, Lorella (Frontiers in Psychology, 2019)
Human behavior must be flexible to respond to environmental and social demands and, to achieve these goals, it requires control. For instance, inhibitory control is used to refrain from executing unwanted or anticipated responses to environmental stimuli. When inhibitory mechanisms are inefficient due to some pathological conditions, such as attention-deficit hyperactivity disorder (ADHD) or pathological gambling, patients show a reduced capability of refraining from executing actions. When planning to execute an action, various inhibitory control mechanisms are activated to prevent the unwanted release of impulses and to ensure that the correct response is produced. A great body of research has used various cognitive tasks to isolate one or more components of inhibitory control (e.g. response selectivity), and to investigate their neuronal underpinnings. However, inter-individual differences in behavior are rarely properly considered, although they often represent a considerable source of noise in the data. In the present review, we will address this issue using the specific case of action inhibition, presenting the results of studies that coupled the so called Go/NoGo paradigm with non-invasive brain stimulation to directly test the effects of motor inhibition on the excitability of the corticospinal system (CSE). Motor preparation is rarely measured in action inhibition studies, and participants’ compliancy to the task’s requests is often assumed, rather than tested. Single pulse transcranial magnetic stimulation (TMS) is a powerful tool to directly measure CSE, whose responsivity depends on both excitatory and inhibitory processes. However, when motor preparation is not measured and the task design does not require participants to prepare responses in advance, fluctuations in CSE levels can be mistaken for active inhibition. One way to isolate motor preparation is to use a carefully designed task that allows to control for excessive variability in the timing of activation of inhibitory control mechanisms. Here we review single pulse TMS studies that have used variants of the Go/NoGo task to investigate inhibitory control functions in healthy participants. We will identify the specific strategies that likely induced motor preparation in participants, and their results will be compared to current theories of action inhibition.